Eye movement desensitisation and reprocessing for childbirth-related post-traumatic stress symptoms: effectiveness, duration and completion - A. Doherty; U. Nagle; J. Doyle; R. M. Duffy; R. M. Duffy (Frontiers in Global Women's Health)
Childbirth-related post-traumatic stress symptoms (CB-PTSS) occur in 12% of women and 3%–6% of mothers meet criteria for childbirth-related post-traumatic stress disorder (CB-PTSD). Eye Movement Desensitisation and Reprocessing (EMDR) therapy has shown promising results in this population. This study sought to assess the effectiveness of EMDR on CB-PTSS and CB-PTSD; to investigate the effect of EMDR duration on symptom reduction; to measure the EMDR completion rate; and to explore sample characteristics that may be associated with completion or effectiveness. A retrospective analysis was conducted of women (n = 34) who commenced EMDR for CB-PTSS or CB-PTSD in an Irish urban maternity hospital. Symptom severity was measured using the Posttraumatic Stress Disorder Checklist (PCL-5) pre- and post-EMDR. Pre-intervention, 64.7% (n = 22) of the sample met criteria for a provisional diagnosis of PTSD. The majority of women (61.8%) demonstrated a ≥ 10 point reduction on PCL-5 following EMDR. There was no correlation between reduction in PCL-5 score and number of EMDR sessions (r = −0.12, p = 0.504). The EMDR completion rate was 70.6%. Analyses did not identify any variables that were associated with EMDR completion or effectiveness. To our knowledge, this is the largest studied sample of women who have received EMDR for CB-PTSD or CB-PTSS. EMDR may be an effective intervention for CB-PTSS and CB-PTSD, even in women with a history of prior trauma, co-morbid mental health problems, or long-term symptoms. EMDR is easily-delivered with a low drop-out rate. Limitations include lack of a control group and long-term follow-up, and statistical analyses were limited by sample size.